Pengaruh Opini Audit, Pergantian Manajemen dan Pertumbuhan Perusahaan Terhadap Auditor Switching Dengan Financial Distress Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Nisa'ul Kaamilah; Tatas Ridho Nugroho; Toto Heru Dwihandoko (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2020)
This research aims to analyze and obtain empirical evidence about the effect of audit opinion, management change and company growth on auditor switching with financial distress as a moderating variable. The population in this study were 90 financial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used purposive sampling, 42 samples were obtained for three years of observation to produce 126 units of analysis. The research data were obtained from audited financial statements, independent auditor's reports and the company's annual report downloaded from the website www.idx.co.id. The data analysis method uses descriptive statistical analysis, logistic regression analysis and Moderated Regression Analysis using SPSS version 22. The results of the study prove that simultaneous audit opinion, management change and company growth influence auditor switching. Partially the change of management and company growth has no effect on auditor switching. While audit opinion has a positive effect on auditor switching. Financial distress is able to moderate the change of management towards auditor switching, but it can’t moderate the relationship between audit opinion and company growth with auditor switching at financial sector companies listed on the Indonesia Stock Exchange in 2017-2019.